The Length and Cost of Banking Crises - Frydl, Edward (IMF Working Papers; Working Paper ;, 1999)
This paper reviews how recent studies of banking crises differ with regard to the dating, length, and costs of the crises. Significant discrepancies in these features suggest the absence of analytical consensus. The data allow an examination of the relation between perceived crisis length, as an index of delay in taking actions to resolve a crisis, and crisis costs. Cross-sectional evidence does not show that the length of a crisis is a significant contributor to its resolution cost. A measure of economic cost, the growth shortfall in the crisis period, shows more evidence of a link.